KECERNAAN IN-VITRO TANAMAN KALIANDRA (Calliandra calothyrsus) BERBUNGA MERAH DAN PUTIH - Anak Agung Ayu Sri Trisnadewi; I Gusti Lanang Oka Cakra (Udayana University, 2015)
The experiment is aimed to evaluate the different of rumen fermentation product and in-vitro digestibility of Calliandra calothyrsus with red and white flower. The different means is analized with t-test (unpairing t-test with equal replicate) and replicate ten times each. Variables observed are pH, NH3, VFA parsial and total, dry matter and organic digestibility in-vitro. Results of the experiment showed that pH value, NH3 concentration and VFA partial and total on Calliandra calothyrsus with red flower tend to lower compared with white one but statistically not significant different. Dry matter and organic digestibility in-vitro of Calliandra calothyrsus with red flower is significantly lower than white one. It could be concluded that rumen fermentation product and dry matter and organic matter digestibility in-vitro of Calliandra calothyrsus with red flower is better than white one.Keywords: Calliandra calothyrsus, ammonia, vollatile fatty acid, in-vitro digestibility